Clinical analysis of drug‐induced sleep endoscopy for the OSA patient. (8th August 2015) - Golbin, Dina; Musgrave, Brandon; Succar, Eric; Yaremchuk, Kathleen
Abstract : Objectives/Hypothesis: To determine if the use of drug‐induced sleep endoscopy (DISE) and transoral robotic surgery (TORS) for the treatment of obstructive sleep apnea (OSA) is associated with improved outcomes and acceptable complication rates when compared to uvulopalatopharyngoplasty (UPPP) with or without tonsillectomy (± T). Methods: A retrospective cohort review was performed comparing 40 patients who had previously undergone UPPP ± T with 64 patients who had DISE, UPPP ± T, and possible TORS base‐of‐tongue resection and/or partial epiglottectomy. Apnea‐hypopnea index (AHI), Epworth Sleepiness Scale (ESS), body mass index, sex, hospital length of stay, hospital charges, hospital readmissions, emergency department visits, and major complications were compared for both groups. Results: The 40 patients who underwent UPPP ± T without DISE showed a significant reduction in AHI of −20.1 ( P  = 0.001) and a complication rate of 3% ( P  = 0.001). There was no significant change in ESS (−2.2; P  = 0.734). The 64 patients who underwent DISE and subsequent procedures showed a significant reduction in AHI of −21.4 ( P  = 0.001) and a complication rate of 34.7% ( P  = 0.001). There was no significant difference in the ESS (+0.1; P  = 0.734) or AHI ( P  = 0.092) between the two groups. Conclusion: Patients who underwent UPPP ± T without DISE did not show a statistically significant difference in outcomes compared to the patients who underwent DISE with other procedures, including TORS. The TORS patients had increased total costs and length of stay that were statistically significant and had increased complications that were not statistically significant. Level of Evidence: 4. Laryngoscope, 126:249–253, 2016